The role of the European Union for the financial integration of Eastern Europe - André Tomfort (Fachhochschule für Wirtschaft Berlin, IMB Institute of Management Berlin, 2006)
The objective of this paper was to investigate the integration of Eastern European financial markets into the EU and world markets. Financial integration has been measured by international investment positions and financial liberalisation measures.
Keywords: 330